Modeling for image processing system validation, verification and testing. - Li, Xing (Software engineering notes.)
State of the art digital copiers and multifunctional devices not only has millions of lines of software code but also employ application specific hardware components each having millions of gates to perform sophisticated image processing functions. To ensure high quality of the system, an image path system model, which contains both an image processing driver model part and a hardware component model part, is constructed. The modeling work not only facilitates system validation, verification and testing but also maximizes the reuse of well-tested artifacts. This paper describes the image path system model and its development process.